2017
DOI: 10.1177/1540796917698832
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the General Education Curriculum in General Education Settings with Students with Severe Disabilities

Abstract: This systematic literature review examined research on stakeholders’ beliefs about addressing the general education curriculum in general education classrooms with students with severe disabilities (SD). The investigation was limited to studies published in peer-reviewed journals between 1997 and 2015. Ten articles were identified and then analyzed using an inductive coding approach and thematic analysis. Secondary data analysis revealed four major themes centered on (a) method of access, (b) type of curriculu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…Preliminary research describes why this trend of persistent exclusion of students with ESN might occur. Teachers continue to identify social inclusion as more important than progress and participation in general education for students with ESN (Ballard & Dymond, 2017); consequently, inclusion in core academic instruction remains a low priority for many teachers.…”
mentioning
confidence: 99%
“…Preliminary research describes why this trend of persistent exclusion of students with ESN might occur. Teachers continue to identify social inclusion as more important than progress and participation in general education for students with ESN (Ballard & Dymond, 2017); consequently, inclusion in core academic instruction remains a low priority for many teachers.…”
mentioning
confidence: 99%
“…Stakeholders' beliefs about addressing the general education curriculum in mainstream classrooms with students with MSCD were investigated by Ballard and Dymond (2017), whose systematic review showed that generally stakeholders perceive social inclusion as more important than involvement in classroom activities and academic progress. Finally, Rogers and Johnson (2018) conducted a systematic review to determine the most effective strategies for including students with MSCD within the general education classroom, and their results showed that an individualised education program within a Universal Design for Learning environment gave access to meaningful and appropriate inclusive education.…”
Section: Previous Reviewsmentioning
confidence: 99%
“…Kuntz and Carter (2019) noted in their meta-analysis that examined middle and highschool aged students that supporting access to both social and educational opportunities continues to be a challenge. This may be due to the fact that, as Ballard and Dymond (2017) stated in a meta-analysis of literature on perceptions and inclusion, that many stakeholders support teaching social skills to students with disabilities in general education classrooms, but are unclear or unsure on how to promote achievement for these students in a manner that is meaningful to the students. Ballard and Dymond (2017) further noted that many educators saw inclusive education as primarily social inclusion, which is needed (Polat, 2011), but is not the only driving factor.…”
Section: Challenges Faced In Implementationmentioning
confidence: 99%
“…This may be due to the fact that, as Ballard and Dymond (2017) stated in a meta-analysis of literature on perceptions and inclusion, that many stakeholders support teaching social skills to students with disabilities in general education classrooms, but are unclear or unsure on how to promote achievement for these students in a manner that is meaningful to the students. Ballard and Dymond (2017) further noted that many educators saw inclusive education as primarily social inclusion, which is needed (Polat, 2011), but is not the only driving factor. The authors stated that traditional inclusion progresses in a manner of physical access to social inclusion and finally to curricular inclusion, this is an interesting juxtaposition to the substantial extent of materials and programs available for curricular access (Ballard & Dymond, 2017).…”
Section: Challenges Faced In Implementationmentioning
confidence: 99%
See 1 more Smart Citation